Functional modification mediated value addition of seaweed polysaccharides – a perspective1. Issue 73 (9th August 2015) - Siddhanta, A. K.; Sanandiya, Naresh D.; Chejara, Dharmesh R.; Kondaveeti, Stalin
<x xml:space="preserve">Abstract</x> Value addition of seaweed polysaccharides by their functional modification with various substrates leading to new effects.